EVALUASI SISTEM AKUNTANSI DENGAN PENDEKATAN SIKLUS UNTUK SISTEM PENGGAJIAN PADA PT PUTRA ABADI SANTOSO DI SURAKARTA - Djoko Kristianto, Johan Purnomo, Aris Eddy Sarwono & (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2012)
ABSTRACT Abadi PT Putra Santoso is a distributor for the products pocari sweat dan soyjoy. The problem in this research is the application of accounting systems for payroll cycle on PT Putra Eternal Solo Santoso was effective. The purpose of this study to evaluate the accounting system implemented payroll cycle Abadi PT Putra Santoso. The usefulness of this study as an input or consideration for companies on the effectiveness of the procedures and systems for payroll cycle that has been run by the company, so that management can take the necessary steps to improve the payroll system in the future. This study used a descriptive comparative method.Â  The data required is the history of PT Putra Abadi Santoso, human resources, organizational structure, finance and accounting.Â  Sources of data in the form of primary data and secondary data. Date collection techniques with observation, interviews, documentation and questionnaires. Data analysis techniques by giving questionnaires to the head of accounting, payroll cycle describes the PT Putra Abadi Santoso, identifying good and weaknesses accounting systems for payroll cycle approach, giving advice and repair procedures of accounting systems for payroll cycle approach. The results obtained in the payroll accounting system PT Putra Abadi Santoso based questionnaire system of internal control can be effective. Keywords: evaluation, accounting systems, payroll, cycle